Shiga Like Toxin 1 (STX-1) Detection From Escherichia coli O157:H7 Local Isolates - Suardana, I W.; Pinatih, K.J. P.; Widiasih, D. A. (Journal of Health Sciences and Medicine; Vol 1 No 2 (2017): JHSM (September 2017)DO - 10.24843/JHSM.2017.v01.i02.p01, 2018)
Shiga-like toxin (Stx) otherwise known as verotoxin and verocytotoxin is a toxin produced by some strains of Escherichia coli particularly by strain O157: H7. This toxin is an AB5 toxin type which is known to have similarities with the toxins produced by Shigella dysenteriae . Stx from E. coli   O157: H7 can be distinguished into stx 1 and stx 2. Stx1is usually associated with most outbreaks and detrimental sporadic cases of illness in humans. In this research, we observed the titer of Shiga toxin (Stx 1 / VT1) from local isolates isolated from cattle and human feces by using vero toxin Escherichia coli -reverse passive latex agglutination test (VTEC-RPLA) method. The results showed local isolates KL-48 (2) of human origin, SM-25 (1) of cattle feces origin and DS 21 (4) of beef origin positively produced VT1 2 units of titer, meanwhile the isolate SM 7 (1) was negative. Titer of toxin Stx1 produced from local isolates was known to be lower when compared to the control isolate ATCC 43894 with 8 units of titer.